Legal Pluralism and Military Justice: A Critical Analysis of Equality Before the Law in Indonesia - Cecilia F. Harsono; Marsetio Marsetio; Anton Nugroho; I Nengah Putra Apriyanto; Faonaso Harefa (Khazanah Hukum, 2026)
The growing public demand in recent years for members of the Indonesian National Armed Forces  to be subject to general courts has become a significant legal issue. This study analyzes the jurisdiction of military courts in Indonesia from the perspective of legal pluralism, with a focus on the principle of equality before the law as part of human rights protection. The existence of military courts based on Law Number 31 of 1997 reflects the principle of lex specialis derogat legi generali; however, the broad scope of their jurisdiction, including authority over ordinary criminal offenses, raises concerns regarding legal equality, accountability, and justice within a democratic rule-of-law system. This research employs a normative legal approach combined with a socio-legal perspective to analyze regulations, legal doctrines, and their practical implementation. The findings indicate a normative disharmony between military court regulations and the principle of equality before the law, as well as a tension between institutional military interests and human rights protection. The dualism of jurisdiction between military and general courts reflects a form of legal pluralism that may be functionally justified, yet it also has the potential to create unequal access to justice. This study proposes a functional reconstruction of jurisdiction, whereby military courts are limited to handling offenses directly related to military duties, while ordinary crimes are considered for transfer to general courts through legal reform, including judicial review at the Constitutional Court, as well as the optimization of Connectivity courts as a transitional model. These findings underscore the importance of regulatory harmonization in order to establish a fair and accountable judicial system.